Compressibility and consolidation behaviors of Dredged Marine Soils (DMS) admixed with cement and/or Waste Granular Materials (WGM) - Rosman, Mohammad Zawawi; Chan, Chee-Ming (Penerbit Uthm, 2018)
Relatively low engineering properties of dredged marine soils (DMS) have rendered the soil as geo-waste which is most likely to be discarded back into the sea. Soil improvement by using cement could easily improve the engineering properties of the soil. However, with the increasing trends of green technology and sustainable engineering, many researchers seek for alternative pozzolanic materials such as coal bottom ash (BA) and palm oil clinker (POC) to fully or partially substitute the use of cement. Therefore, series of one-dimensional consolidation test were executed on samples with various percentages of admixtures in the present study. This study examines the compressibility and time-dependent consolidation behaviour of the samples. Based on the findings, cemented DMS shows higher void ratio than WGM-admixed DMS. The cement-WGM-admixed samples display considerable compressibility and time-dependent consolidation properties. Moreover, the addition of BA in cement-admixed DMS could reduce the usage of 5 % cement. These findings suggest that in general, WGM could be act as supplementary additives to cement.